Analisis Profitabilitas Dan Kelayakan Usaha: Studi Kasus Pada Pedagang Pinang Di Pasar Tradisional Wamena - Meri Berliana; Maria Gabriela Mbinu; Inrianti Inrianti; Sepling Paling (JURNAL VIGOR, 2026)
This study aims to analyze the feasibility of the areca nut trading business in Wamena. The study employed a quantitative descriptive approach. The research sample consisted of 20 respondents who were active areca nut traders in Wamena. Data were collected through observation, interviews, and questionnaires. The analysis focused on market, technical, and financial aspects, including profit analysis, Revenue-Cost (R/C) Ratio, and Break Even Point (BEP). The results showed that the traders’ average total revenue was IDR 350,000 per day, while the average total cost was IDR 220,000 per day, resulting in an average profit of IDR 130,000 per day. The R/C Ratio value of 1.57 indicates that the business is economically feasible because it is greater than 1. In addition, the Break Even Point analysis showed that the minimum production required to reach the break-even point was 24 bundles per day, while the actual production level was around 100 bundles per day, indicating a safe profit zone. Based on the findings, it can be concluded that the areca nut trading business in Wamena is feasible and profitable. This business has strong market demand, simple operational procedures, and stable financial performance. Therefore, it is recommended that traders continue and expand their business in order to improve their economic welfare.